ChemInform Abstract: Expanding the Scope of Primary Amine Catalysis: Stereoselective Synthesis of Indanedione‐Fused 2, 6‐Disubstituted trans‐Spirocyclohexanones. Issue 31 (14th July 2016) - Madhusudhan Reddy, G.; Ko, Chi‐Ting; Hsieh, Kai‐Hong; Lee, Chia‐Jui; Das, Utpal; Lin, Wenwei
Abstract: Mechanistic investigation of these organo‐catalytic spirocyclizations reveals two competing pathways: a concerted Diels—Alder reaction and a stepwise Michael addition.